2017
DOI: 10.3390/ijerph14060631
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Community Water Fluoridation with Caries Prevalence and Oral Health Inequality in Children

Abstract: This study aimed to confirm the association between the community water fluoridation (CWF) programme and dental caries prevention on permanent teeth, comparing to a control area, neighbouring population without the programme, and verifying whether the programme can reduce the socio-economic inequality related to the oral health of children in Korea. Evaluation surveys were conducted among 6-, 8-, and 11-year-old children living in Okcheon (CWF) and neighbouring Yeongdong (non-CWF, control area) towns in South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 34 publications
1
26
0
2
Order By: Relevance
“…These results are mostly consistent with those of previous studies performed in various countries, including the U.S. [13][14][15][16][17][18]. Cho et al [13] and Kim et al [14] showed that socioeconomic inequality exists in non-CWF areas but not in CWF areas in Korea. Cho [15] conducted their study in Australia and explored dental health disparities based on income and race.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These results are mostly consistent with those of previous studies performed in various countries, including the U.S. [13][14][15][16][17][18]. Cho et al [13] and Kim et al [14] showed that socioeconomic inequality exists in non-CWF areas but not in CWF areas in Korea. Cho [15] conducted their study in Australia and explored dental health disparities based on income and race.…”
Section: Discussionsupporting
confidence: 91%
“…We believe that education status is equally as important as income status in disparities studies [3]. Thus, because of the nature of our studies' strengths, we believe our findings add valuable information to the existing literature [13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Parents were asked to provide information about their educational levels via a three-item list (primary education (6 years); secondary education (9-12 years); higher education (≥15 years)). Besides the parental educational level, the Family Affluence Scale (FAS) [45,46] was used to assess SES, since, based on family consumption, it appears to be more ecologically valid than parental income [47,48]. The FAS has been validated and used in several countries, including Greece [48].…”
Section: Socio-economic Characteristicsmentioning
confidence: 99%